PERANCANGAN DESIGN PROTOTYPE ABSENSI ONLINE PADA KELAS lX-4 SMP NEGERI 2 TANAH JAWA MENGGUNAKAN METODE DESIGN THINKING - Winda Septiana Simangunsong; Ruly Dwi Arista; Randi Rian Putra (CV. Hawari, 2025)
The development of information technology in the era of Industry 4.0 Revolution has driven digitalization in various sectors, including education. This study aims to design a prototype of an online attendance system based on the web as a solution to the problems of manual attendance systems still used in SMP Negeri 2 Tanah Jawa. The identified problems include the potential for data manipulation, lack of efficiency, and difficulties in managing and reporting attendance data. The method used in this study is Design Thinking, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. The design process was carried out using Figma, Balsamiq, and Canva software. The resulting prototype design includes features such as login, account registration, lesson schedule display, daily attendance filling, and student profile. The design results show that the system is able to improve efficiency, accuracy, and transparency in the process of recording student attendance. It is hoped that this design will become the basis for the development of an online attendance system in reality and can support efforts to digitalize school administration. Further recommendations include integrating the system with notifications to parents and analyzing attendance data based on graphics for improved monitoring